KESADARAN HUKUM, PSYCHO ADVERTISING DAN PSYCHOPRENEURSHIP - Divania Fazrina; Maharani Amelia Firjatullah, Afrizal Qimas Chairi, Isna Faradilla, Al Fachri Nurfath, Evani Alvi Nug (JOURNAL OF COMMUNITY DEDICATION, 2024)
The "Legal Awareness, Psycho Advertising, and Psychopreneurship" Community Service Program (KKN) seeks to improve community knowledge on legal issues, innovative marketing strategies, and psychology-driven entrepreneurship. This study adopts a qualitative descriptive method with a direct participatory approach. The program included two days of seminars: the first day focused on psychopreneurship and creative marketing to support MSME development, while the second day addressed domestic violence (DV) issues, including victims' rights and legal procedures for offenders. Findings reveal that the participatory approach successfully enhances student-community engagement, strengthens legal awareness, and offers practical guidance for business growth. The program concludes with recommendations to develop similar initiatives, aiming to foster a legally aware and economically self-reliant community in the future.